Analysis of contextual teaching and learning (CTL) in the course of applied physics at the mining engineering department - Fadhilah Fadhilah; Z. Mawardi Effendi; Ridwan Ridwan (International Journal of Science and Applied Science: Conference Series, 2017)
Applied Physics is used to comprehend any other technical engineering studies and as the foundation of technology innovation. As one of the curriculum components in helping the students to be competent in certain skills, it is used to develop intellectual, attitude, interest, skill and creativity. Physics is a course containing materials in form of fact, concept, principle and procedure. The method used in this research was literature studies and observation. The purpose of the research was to analyze whether the seven CTL principles are needed in Applied Physics or it can be simplified. The seven principle used in Indonesia are constructivism, inquiry, questioning, learning community, modelling, reflection and authentic assessment. Having conducting literature studies, especially for Applied Physics, inquiry can be applied along with questioning. Modelling is not the priority because Applied Physics does not need the real model, but only needs an example for Mining Engineering. Meanwhile, reflection has been accommodated in every learning step. Conclusively, constructivism, inquiry and questioning, learning community and authentic assessment are the steps needed during the learning of Applied Physics using CTL approach.